A median voter model of health insurance with ex post moral hazard - Johanna Jacob; Douglas Lundin (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
One of the main features of health insurance is moral hazard, as defined by Pauly (1968); people face incentives for excess utilization of medical care since they do not pay the full marginal cost for provision. To mitigate the moral hazard problem, a coinsurance can be included in the insurance contract. We analyze under what conditions there is a conflict between individuals on what coinsurance rate should be set with public health insurance, and we establish conditions for a median-voter equilibrium. Then we allow the public insurance to be supplemented with private insurance, and we establish conditions under which public provision will lead to larger aggregate spending than private provision does.
Keywords: H42; I18; 330; health insurance; moral hazard; public provision; median voter; Krankenversicherung; Versicherungsökonomik; Moral Hazard; Median Voter; Theorie